Pengaruh Pendidikan Kesehatan Terhadap Kepatuhan Ibu Melakukan Pemeriksaan Inspeksi Visual Asam Asetat (Iva Test) Di Puskesmas Suli - Kartini S (STIKes Ibnu Sina Ajibarang, 2023)
Cervical cancer is the most common health problem in women, where special attention is needed to prevent this health problem. One effort that can be done to recognize pre-cancerous lesions early is by conducting an Acetic Acid Visual Inspection (IVA) examination which can reduce the incidence of morbidity and maternal mortality caused by cervical cancer. This IVA examination is very easy and practical to be carried out either by midwives or professional health workers (doctors) who can be obtained at health facilities such as clinics, health centers and hospitals. This study aims to determine the effect of health education on maternal adherence to visual inspection of acetic acid at the Suli Health Center. This research method is analytic with design Quasi Experiment (experiments pseudo), with design one group pretest posttest . The population in this study were all women of childbearing age (WUS) who were in the work area of the Suli Health Center as many as 78 people and the sample in this study were all WUS who were in the work area of the Suli Health Center who had certain characteristics, namely women of childbearing age who had active sexual relations. with the number of samples in this study amounted to 30 people. Sampling was carried out using purposive sampling method. This research was processed using a computerized system with the help of the SPSS program. The data analysis method used was statistical test analysis with the Wilcoxon signed ranks test to determine the effect of health education on WUS compliance by conducting an IVA examination where if obtained The p value of this test or p 0.000 <0.05, can be interpreted as significant. Therefore, it is recognized that health education has an impact on WUS adherence to carrying out IVA examinations.